USING PRACTICE POSTERS TO IMPROVE STUDENTS’ SPEAKING SKILL - Farisha Andi Baso; Reskiwati Amelia (Universitas Muhammadiyah Makassar, 2014)
This research was aimed to explain the improvement of the students’ speaking fluency and the students’ speaking accuracy through the of discussion technique in teaching speaking. The research was implemented in SMP Pondok Pesantren Darul Aman Gombara Makassar at the eighth-grade students through a classroom action research (CAR). The researcher took 33 students as the subject of the research. The researcher taught speaking English using practice posters. To find the results, the researcher got the information from the students’ answers on oral test in the form of D-test, the test of a cycle I and test of cycle II. The result of the research using Practice Posters showed that the researcher used the CAR (Classroom Action Research) principle to collect the data. The research conducted through two cycles with each cycle consisted of four meetings. By implementing Practice Posters as a media in teaching speaking, the students had chanced to be active and cooperative in learning speaking so that the students’ speaking accuracy and the students’ speaking fluency achievement were improved significantly. It could be seen from the result of the students’ activities during the action, and the students’ speaking achievement in speaking. The mean score of the students’ speaking D - Test was 3.67. It was categorized as fair classification (low ability). While the mean score of the students’ speaking test in cycle I was 5.02. It is higher than the mean score of the students’ speaking test. But the result was not significant from the result which was expected according to the background namely 6.5, so the research was continued to the cycle II and the mean score of the students’ speaking achievement of cycle II was 7.16. It was categorized as good. It also indicated that there was a significant score from the result expected in the background namely 6.5. The result above was acquired from the students’ speaking ability in terms of speaking accuracy and speaking fluency.